DESKRIPSI HASIL MENULIS TEKS ULASAN DALAM PEMBELAJARAN DARING DENGAN MENGGUNAKAN METODE STUDENT TEAMS ACHIEVEMENT DIVISIONS - Komalasari, Eulis; Wikanengsih, Wikanengsih; Ismayani, Mekar (IKIP Siliwangi, 2021)
This study describes online learning to write review texts using themethod Student Teams Achievement Divisions. Online learning is a distance learning method that has a major and significant influence in the world of education, thus teachers must innovate the learning process. In learning to write students still have difficulty in developing ideas and using language. So the researchers provided innovations in the online learning process to write review texts using themethod Student Teams Achievement Divisions. The research aimed to describe the results of the performance ofstudents, research method used is descriptive qualitative. Sample in this study was class VIII F at SMPN 2 Cimahi, amounting to 29 students. The results of this study obtained 5 students got a high score and 25 students got a sufficient score with an average value of 83, it can be concluded that the use of themethod Student Teams Achievement Divisions suitable for use in online learning material to write the review text in class VIII F.